Atmospheres of Dwelling. Phenomenologies of “Being-at-Home” - De Matteis, Federico (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
First introduced by Martin Heidegger in his later philosophical work, over the decades the concept of dwelling has acquired a fundamental importance in architectural theory. Its “classic” status, however, along with its centrality in post-modern architecture, has largely prevented the unfolding of an open discussion on the present-day validity of this notion. Similarly, the work of another cult author such as Gaston Bachelard, whose book The Poetics of Space is equally revered as a classic, appears to be uncritically espoused outside of a proper contextualization. While dwelling does represent a fundamental driver of human presence in the world, these two primary accounts and their implications in design should be discussed against other complementary or antagonistic models, such as those proposed by Deleuze and Guattari, Sloterdijk and Schmitz. Each of these authors defines his position vis-à-vis Heidegger’s original proposal, while opening to different repercussions on the practices of design.